They (Don’t) Need Us: Functional Indispensability Impacts Perceptions of Representativeness and Commitment When Lower-Status Groups Go Through an Intergroup Merger - Rosa, Miriam; Giessner, Steffen; Guerra, Rita; Waldzus, Sven; Kersting, Anna-Maria; Veličković, Katarina; Collins, Elizabeth C. (Frontiers in Psychology, 2020)
Intergroup changes occur often between subgroups who are asymmetric in status (e.g., size, power, prestige), with important consequences for social identification, especially among the members of lower-status groups. Mergers offer an example of such changes, when subgroups (merger partners) merge into a common, superordinate group (post-merger group). Lower-status subgroups frequently perceive they are less represented in the post-merger group, therefore committing less to the changes a merger implies. Five studies offered an intergroup relations’ perspective on mergers (N’s= 479, 150, 266, 113 and 229 respectively), examining how functional indispensability (instrumental contribution of the ingroup) positively influences perceptions of representativeness in the post-merger group (relative ingroup prototypicality), which, in turn, affect post-merger identification and, finally, change commitment. Additionally, the role of cognitive information processing (heuristic vs systematic) on prototypicality was explored. Results suggest that functional indispensability impacts relative ingroup prototypicality (Studies 1-5), and this may be moderated by information processing (Study 2). Moreover, prototypicality and identification with the superordinate post-merged group mediated the effect of functional indispensability on change commitment (Studies 1-3). These findings provide important theoretical insights into prototypicality perceptions held by lower-status merger-partners and minority groups in general, by identifying functional indispensability as a source of prototypicality other than relative status. In addition, by proposing a functional approach to the relations between social groups, these findings suggest better practices for managing structural changes, such as combining sources of strategic/functional and identity fit when announcing an intergroup change.